Configurable Memory Protection by Aspects - Lohmann, Daniel; Hofer, Wanja; Spinczyk, Olaf; Schröder-Preikschat, Wolfgang; et al. (Proceedings of the 4th Workshop on Programming Languages and Operating Systems (PLOS 2007), 2007)
We describe the implementation of memory protection by means of aspect-oriented programming (AOP) in CiAO, an AUTOSAR-like family of embedded operating systems. The use of AOP was originally motivated by the fact that memory protection is a cross-cutting policy, which, furthermore, has to be configurable at build-time in AUTOSAR. We learned, however, that besides switching between full protection and no protection, an AOP-based approach also makes it easy to apply completely different models of protection. For the domain of statically configured embedded systems, where certain failure scenarios can often be excluded by means of code analysis or even probability, this facilitates tailored and light-weight "nav-as-vou-use" protection strateaies Copyright 2007 ACM.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD4.config
Keywords: Aspect-Oriented Programming (AOP); AspectC++; CiAO; Configurability; Aspect-Aware Operating System; Memory Protection